2018
DOI: 10.1007/s11596-018-1923-0
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Cycle with or without a Depot Gonadotropin-releasing Hormone Agonist for Frozen-thawed Embryo Transfer: An Assessment of Infertility Type that Is Most Suitable

Abstract: The clinical outcomes of five groups of infertility patients receiving frozen-thawed, cleavage-stage embryo transfers with exogenous hormone protocols with or without a depot gonadotropin-releasing hormone (GnRH) agonist were assessed. A retrospective cohort analysis was performed on 1003 cycles undergoing frozen-thawed, cleavage-stage embryo transfers from January 1, 2012 to June 31, 2015 in the Reproductive Medicine Center of Wuhan General Hospital of Guangzhou Military Region. Based on the infertility etiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Furthermore, no data were presented on live birth rate. In contrast, however, a larger sample study by Xie and colleagues 14 with many patient subgroups found a significantly higher clinical pregnancy rate, ongoing pregnancy rate, and live birth rate in the PCOS subgroup ( n = 156) receiving GnRH‐a pretreatment than in PCOS patients not receiving GnRH‐ pretreatment. One possible mechanism underlying these reported benefits of GnRH‐a pretreatment for PCOS is suppression of serum LH level, serum E2 level and GnRH–HCG axis function with subsequent inhibition of endometrial inflammation and enhanced expression of endometrial adhesion molecules.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, no data were presented on live birth rate. In contrast, however, a larger sample study by Xie and colleagues 14 with many patient subgroups found a significantly higher clinical pregnancy rate, ongoing pregnancy rate, and live birth rate in the PCOS subgroup ( n = 156) receiving GnRH‐a pretreatment than in PCOS patients not receiving GnRH‐ pretreatment. One possible mechanism underlying these reported benefits of GnRH‐a pretreatment for PCOS is suppression of serum LH level, serum E2 level and GnRH–HCG axis function with subsequent inhibition of endometrial inflammation and enhanced expression of endometrial adhesion molecules.…”
Section: Discussionmentioning
confidence: 82%
“…Although FET is used more frequently than fresh cycle embryo transfer for women with PCOS due to the significantly increased risk of OHSS, 2 little interest has been paid to the development of a suitable endometrial preparation protocol for FET in this clinical population. To date, only two prospective studies (one RCT 17 and one observational study without a comparison group 13 ) and three retrospective studies 13 15 have compared endometrial preparation methods for FET in women with PCOS. Among these studies, one RCT 17 and one large sample retrospective study 18 compared ovulation induction and artificial cycle methods using exogenous steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 28 days interval between the administration of GnRHa and estrogen was thought to be su cient as the pituitary suppression exerted by GnRHa was relieved upon embryo implantation, wherein the GnRHa-HCG system could play an important role in embryo implantation and development [23]. Palmerola et al administered 1000 mg of leuprolide acetate on day 2 of the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…With AC, the time of administering exogenous oestradiol and progesterone and the quantities used can be carefully planned, making clinical arrangements more accurate and flexible. In addition, early ovulation induced by a spontaneous LH surge can be avoided by combining AC with GnRH-a [31]. However, AC is expensive and usually requires daily injections, which can be tedious for both medical staff and patients [32].…”
Section: Discussionmentioning
confidence: 99%